Una teología samaritana: El estilo teológico de Jon Sobrino (Teología, 2020)
This paper intends to present the fundamental notes of Jon Sobrino’s theology. Its uniqueness lies in the approach in terms of style. The author believes that the Jesuit priest’s work has become an original and creative identity that can be categorized as style. One of the strong thesis of this paper is the definition of Sobrino’s theology as “style”. After establishing the fundamentals of stylistic approach which derives mainly from H. U. von Balthasar and Ch. Theobald, the author unfolds the theological identity of this particular style and its characteristics. The other strong thesis is that the historical reality of suffering in Latin America configures Jon Sobrino’s theological style. Logos and pathos converge into a single movement that qualifies his theology as samaritan theology or sentient theology (X. Zubiri).
Keywords: Jon Sobrino; Theology in Context; Suffering; Logos; Pathos